Languages in Contact : A Study of Arabic Loanwords in Malay/Indonesian Language - Mulyani, Rozanna; Noor, Noordin Mohd (Talenta Publisher, 2018)
This paper discusses the contact language between Malay and Arabic language. Objectives of the study are to look into the similarities etymology of the two countries national language. This paper will implement qualitative analysis which is based on discussions and comparison. The results of this study show that cultural contact especially the reach of Islam in Southeast Asia results in linguistic contact. Linguistic borrowing in most cases exhibits as a response to language borrowing. A number of motivations stand behind the phenomenon of borrowing. As a result of cultural and linguistic contact between Malay language as a lingua franca of the region in the early days and Arabic languages so many Arabic words absorbs into Malay languages.